2020
DOI: 10.12669/pjms.36.5.1995
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative predicting factor in visual outcome after macular hole surgery

Abstract: Objective: To determine the effectiveness of macular hole index (MHI) as a predicting factor of visual outcome after full thickness macular hole surgery. Methods: This quasi-experimental study was conducted at LRBT Free Base Eye Hospital, Karachi from January 2018 to March 2019. Total 45 eyes of 45 patients with full thickness macular hole (FTMH) underwent preoperative Best Corrected Visual Acuity (BCVA) assessment with logMar chart and Optical Coherence Tomography (OCT) scanning, with measurement of bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Of 17 patients (HFF > 0.9), 10 (58.82%) patients showed macular hole closure and 7 (41.17%) were remain unclosed. Haritoglou et al 17 also reported the similar results as we find in our study that higher values of HFF are associated with good post-surgical outcomes Feroz et al 9 reported that MHI >0.5 is associated with good visual outcomes. Haroon Tayyab et.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Of 17 patients (HFF > 0.9), 10 (58.82%) patients showed macular hole closure and 7 (41.17%) were remain unclosed. Haritoglou et al 17 also reported the similar results as we find in our study that higher values of HFF are associated with good post-surgical outcomes Feroz et al 9 reported that MHI >0.5 is associated with good visual outcomes. Haroon Tayyab et.…”
Section: Discussionsupporting
confidence: 89%
“…8 Nowadays OCT (optical coherence tomography) has been playing a pivotal role in macular hole diagnosis and analyzing its preoperative role in visual and anatomical outcomes of macular hole surgery. 9 Ip et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with MHI < 0.5, the MHI ≥ 0.5 indicates a better visual acuity (ref. 30,31). THI is expressed as the ratio of hole height to minimum diameter, which also re ects the ratio of traction in the perpendicular direction to that in the tangent direction.…”
Section: Discussionmentioning
confidence: 99%